Phylogeny, host use, and diversification in the moth family Momphidae (Lepidoptera: Gelechioidea) - Bruzzese, Daniel J. (PLoS One, 2019)
Insect herbivores and their hostplants constitute much of Earth’s described biological diversity, but how these often-specialized associations diversify is not fully understood. We combined detailed hostplant data and comparative phylogenetic analyses of the lepidopteran family Momphidae to explore how shifts in the use of hostplant resources, not just hostplant taxon, contribute to the diversification of a phytophagous insect lineage. We inferred two phylogenetic hypotheses emphasizing relationships among species in the nominate genus, Mompha Hübner. A six-gene phylogeny was constructed with reared exemplars and collections from hostplants in the family Onagraceae from western and southwestern USA, and a cytochrome c oxidase subunit 1 (COI) phylogeny was inferred from collections and publicly available accessions in the Barcode of Life Data System. Species delimitation analyses combined with morphological data revealed ca. 56 undescribed species-level taxa, many of which are hostplant specialists on Onagraceae in the southwestern USA. Our phylogenetic reconstructions divided Momphidae into six major clades: 1) an Onagraceae flower- and fruit-boring clade, 2) a Melastomataceae-galling clade, 3) a leafmining clade A, 4) a leafmining clade B, 5) a Zapyrastra Meyrick clade, and 6) a monobasic lineage represented by Mompha eloisella (Clemens). Ancestral trait reconstructions using the COI phylogeny identified leafmining on Onagraceae as the ancestral state for Momphidae. Our study finds that shifts along three hostplant resource axes (plant taxon, plant tissue type, and larval feeding mode) have contributed to the evolutionary success and diversification of momphids.